Continuing medical education of family doctors through distance learning in Ukraine - Korzh, Oleksii (Technium Social Sciences Journal, 2021)
Analysis of the state of scientific elaboration of the problem of distance learning in Ukraine and the experience of its implementation in the practice of higher education showed that despite some achievements, this pedagogical problem needs further research. Distance learning improves postgraduate training of doctors. The main purpose of teaching in postgraduate education is to achieve high-quality practical training based on knowledge, skills and abilities in traditional and modern educational technologies. Distance learning is a promising form of pedagogical technologies in the field of medical education, as it is more flexible and corresponds to modern realities of society.